2015
DOI: 10.1007/s10620-015-3700-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Biomarker Expression in Colonic Mucosa with Disease Phenotype in Crohn’s Disease and Ulcerative Colitis

Abstract: Background Inflammatory bowel diseases (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), are characterized by chronic intestinal inflammation due to immunological, microbial and environmental factors in genetically predisposed individuals. Advances in the diagnosis, prognosis and treatment of IBD require the identification of robust biomarkers that can be used for molecular classification of diverse disease presentations. We previously identified five genes, RELA, TNFAIP3 (A20), PIGR, TNF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…PIgR KO mice have enhanced ileal IFNγ and iNOS levels compared to controls [ 53 ], likely because of the increases in certain immune cell subsets. Given alterations in antigen-presenting cells and inflammatory mediators in pIgR KO mice, it is hardly surprising then, that inflammatory diseases such as chronic obstructive pulmonary disease [ 55 , 60 , 61 , 62 ], DSS-induced and T-cell-mediated colitis in mice [ 58 , 63 ], as well as Crohn’s disease and ulcerative colitis in humans [ 64 , 65 ] are highly prevalent when SIgs are absent or reduced. Alterations to the immune baseline of the pIgR KO mice may also be beneficial or detrimental during infection.…”
Section: Lessons From Pigr-deficient Micementioning
confidence: 99%
“…PIgR KO mice have enhanced ileal IFNγ and iNOS levels compared to controls [ 53 ], likely because of the increases in certain immune cell subsets. Given alterations in antigen-presenting cells and inflammatory mediators in pIgR KO mice, it is hardly surprising then, that inflammatory diseases such as chronic obstructive pulmonary disease [ 55 , 60 , 61 , 62 ], DSS-induced and T-cell-mediated colitis in mice [ 58 , 63 ], as well as Crohn’s disease and ulcerative colitis in humans [ 64 , 65 ] are highly prevalent when SIgs are absent or reduced. Alterations to the immune baseline of the pIgR KO mice may also be beneficial or detrimental during infection.…”
Section: Lessons From Pigr-deficient Micementioning
confidence: 99%
“…Studies conducted so far analyzing the expression levels of cytokines and transcription factors in mucosa revealed that CD has been associated with an impairment of Th1/Th17 response [ 8 ], whereas UC has been associated with a Th2/NKT cell response [ 9 ]. Other genes have been indicated as putative differential biomarkers, including α -defensin-5 [ 10 ], circadian genes [ 11 ], TNFAIP3, PIGR, TNF, and PIGR [ 12 ]. Other studies based on RNA-seq approaches revealed important transcriptomic differences between normal mucosa, noninflamed CD mucosa, and inflamed CD mucosa [ 13 ] as well as differences among colon biopsies from CD patients, UC patients, and non-IBD controls [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…IL-8 is vital in the induction of colonic in ammation and has been implicated in the IBD disease activity [13]. The previous studies showed that in UC patients, CXCL8 was particularly upregulated in the in amed mucosa, relative to the non-in amed mucosa [14][15][16].The gene Deleted in Malignant Brain Tumors 1 (DMBT1), which is found in chromosome 10q25.3-q26.1, is regarded as a tumor suppressor because of its homologous deletions and downregulation in lung cancer, medulloblastoma, gastrointestinal cancers, and glioblastoma multiforme [17,18] The existing researches have con rmed the relationship between DMBT1 and UC. Treatment with IL-22 promoted DMBT1 expression by inducing the phosphorylation of STAT3 tyrosine, as well as activation of NF-κB, suggesting the IL-22/DMBT1 axis might play a vital function in UC pathophysiology [19].…”
Section: Discussionmentioning
confidence: 99%